The German Imperial Tax on the Unearned Increment - Brooks, Robert C. (Quarterly Journal of Economics, 1911)
Recent development of this form of taxation in Germany, 683. — The action of the Reichstag, 684. — The law of Feb. 14, 1911, 685. — Exemptions, 685. — Computation of unearned increment, 686. — Original cost and permanent improvements, 687. — Retroactive provisions, 689. — Additions allowed to cost of improvements, 693. — Allowance for change in purchasing power of money, 695. — Selling price and deductions therefrom, 695. — Tax rates, 696. — Summary illustration of working, 697. — Revenue divided among Empire, states, and cities, 700. — Treatment of existing taxes of the same kind, 704. — Administration, 706. — Probable revenue, 707. — Conclusion, 708.